Improving Efficiency In Small Construction Projects: A Project Management Body Of Knowledge Approach - Mutiara Alena Azizah; Gatot Yudoko (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Indonesia’s construction sector relies on foreign investment and meeting international standards for quality, safety, and sustainability, which boosts competitiveness in large-scale infrastructure. This study examines CV. PPA, a construction company in East Java, focusing on the Type 48 housing project. Using the Project Management Body of Knowledge (PMBOK) framework, specifically in Project Scope Management and Project Integration Management, the research identifies key inefficiencies in scope definition, resource allocation, and activity integration. Data were gathered through interviews with the company’s Director and other employees, analyzed with PMBOK, and used to propose project improvements and derive lessons for future initiatives. Findings highlight practical insights to enhance CV. PPA’s project efficiency and offer recommendations for other companies within Indonesia's construction sector, emphasizing structured project management to achieve sustainable growth.